Ab initio simulations on N and S co-doped titania nanotubes for photocatalytic applications. (13th August 2015) - Chesnokov, Andrei; Lisovski, Oleg; Bocharov, Dmitry; Piskunov, Sergei; Zhukovskii, Yuri F; Wessel, Michael; Spohr, Eckhard
Abstract: In this paper we present the results of quantum chemical modeling for energetically stable anatase (001) TiO2 nanotubes, undoped, doped, and codoped with N and S atoms. We calculate the electronic structure of one-dimensional (1D) nanotubes and zero-dimensional (0D) atomic fragments cut out from these nanotubes, employing hybrid density functional theory with a partial incorporation of an exact, nonlocal Hartree–Fock exchange within the formalism of the linear combination of atomic orbitals, as implemented in both CRYSTAL and NWChem total energy codes. Structural optimization of 1D nanotubes has been performed using CRYSTAL09 code, while the cut-out 0D fragments have been modelled using the NWChem code. The electronic properties of the studied systems prove that the band structure of the pristine TiO2 nanotube can be substantially modified by introducing substitutional impurity defects. The N-doped nanotube creates a midgap state that largely has a nitrogen character. The S-doped nanotube has a defect state that almost coincides with the top of the valence bond for the pristine material. For nanotubes codoped with both S and N, we observe a downward shift of the gap state of nitrogen relative to the purely N-doped state by about 0.3 eV. This results in a system with a filled gap state about 0.3 eV below the O2 /H2 O oxidation level, making it a very promising candidate for photocatalytic hydrogen generation under visible light, because due to the presence of sulfur, the bottom of the conduction band is only about 2.2 eV above the occupied midgap state, and also, clearly above the standard hydrogen electrode level.